Unexpected high selectivity for acetate formation from CO2 reduction with copper based 2D hybrid catalysts at ultralow potentials. Issue 46 (17th November 2021) - Cai, Rongming; Sun, Mingzi; Ren, Jiazheng; Ju, Min; Long, Xia; Huang, Bolong; Yang, Shihe
Abstract : A two-dimensional (2D) copper hybrid catalyst (Cu/Cu x OF) composed of metallic Cu well dispersed on 2D F-doped Cu x O nanoplates (Cu x OF) is reported, which shows high catalytic activity toward the CO2 RR for acetate generation. Abstract : Copper-based catalysts are efficient for CO2 reduction affording commodity chemicals. However, Cu(i ) active species are easily reduced to Cu(0) during the CO2 RR, leading to a rapid decay of catalytic performance. Herein, we report a hybrid-catalyst that firmly anchors 2D-Cu metallic dots on F-doped Cu x O nanoplates (Cu x OF), synthesized by electrochemical-transformation under the same conditions as the targeted CO2 RR. The as-prepared Cu/Cu x OF hybrid showed unusual catalytic activity towards the CO2 RR for CH3 COO − generation, with a high FE of 27% at extremely low potentials. The combined experimental and theoretical results show that nanoscale hybridization engenders an effective s, p-d coupling in Cu/Cu x OF, raising the d-band center of Cu and thus enhancing electroactivity and selectivity for the acetate formation. This work highlights the use of electronic interactions to bias a hybrid catalyst towards a particular pathway, which is critical for tuning the activity and selectivity of copper-based catalysts for the CO2 RR.